2007
DOI: 10.1093/ndt/gfm798
|View full text |Cite
|
Sign up to set email alerts
|

Identifying patients with type 2 diabetes at high risk of microalbuminuria: results of the DEMAND (Developing Education on Microalbuminuria for Awareness of reNal and cardiovascular risk in Diabetes) Study

Abstract: Methods. Fifty-five Italian diabetes outpatient clinics enrolled a sample of patients with type 2 diabetes, without urinary infections and overt diabetic nephropathy. A morning spot urine sample was collected to centrally determine the urinary albumin/creatinine ratio (ACR). A tree-based regression technique (RECPAM) and multivariate analyses were performed to investigate interaction between correlates of MAU. Results. Of the 1841 patients recruited, 228 (12.4%) were excluded due to the presence of urinary inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 21 publications
3
17
0
2
Order By: Relevance
“…The prevalence of albuminuria among the HIV-infected subjects without diabetes was similar to the 11% identified by Szczech and colleagues in a similar HIV-infected cohort [13]. The prevalence of albuminuria noted among the uninfected controls with diabetes was slightly lower than other large diabetes cohort studies [14], [16], but the duration of diabetes in our study population was relatively short by comparison and may account for this difference. We did not identify an increased prevalence of albuminuria related to African American race or Hispanic ethnicity as seen in prior large US population surveys [17].…”
Section: Discussionsupporting
confidence: 84%
“…The prevalence of albuminuria among the HIV-infected subjects without diabetes was similar to the 11% identified by Szczech and colleagues in a similar HIV-infected cohort [13]. The prevalence of albuminuria noted among the uninfected controls with diabetes was slightly lower than other large diabetes cohort studies [14], [16], but the duration of diabetes in our study population was relatively short by comparison and may account for this difference. We did not identify an increased prevalence of albuminuria related to African American race or Hispanic ethnicity as seen in prior large US population surveys [17].…”
Section: Discussionsupporting
confidence: 84%
“…A recent comprehensive review of adult randomized controlled trials between 1960 and 2012 reporting major cardiovascular or renal outcomes reinforced the importance of renin-angiotensin system blocker therapy in patients with type 2 diabetes who have an enhanced risk for cardiovascular disease (30). Similar reports regarding early hypertension and renal comorbidities associated with type 2 diabetes in youth are limited (9,11,26). …”
Section: Discussionmentioning
confidence: 70%
“…Recent epidemiological studies suggest that visceral obesity is also associated with increased risk of incident chronic kidney disease (CKD) [7,8]. We and others have previously demonstrated that increased waist circumference, an essential component of the metabolic syndrome, is closely and independently associated with microalbuminuria in patients with type 2 diabetes [5,9]. In addition, two large cohort studies of type 1 and type 2 diabetes clarified that increased waist circumference was significantly associated with incident microalbuminuria [10,11].…”
Section: Introductionmentioning
confidence: 97%
“…Microalbuminuria is a sensitive and potent prognostic marker to evaluate not only the risk of overt nephropathy but increased cardiovascular disease in patients with diabetes [1]; however, its pathogenesis is largely unknown and likely multifactorial [2][3][4][5]. Obesity, especially visceral obesity, has long been recognized as a risk factor for cardiovascular diseases [6].…”
Section: Introductionmentioning
confidence: 99%